Advancing biomedical substrate engineering: An eco-friendly route for synthesizing micro- and nanotextures on 3D printed Ti–6Al–4V - A. Kityk; M. Hnatko; V. Pavlik; M. Balog; J. Šoltys; M. Labudova (Journal of Materials Research and Technology, 2024)
This study investigates the impact of a combined approach involving sandblasting and electrochemical surface treatment using a deep eutectic solvent Ethaline, a eutectic mixture of choline chloride and ethylene glycol, on the surface characteristics of Ti–6Al–4V biomedical substrates fabricated through direct selective laser melting (DSLM). Research has focused on surface morphology, topography, chemical composition, and cell adhesion. The novel approach demonstrated the ability to create a hierarchical surface structure with both micro and nanopatterns. The rough edges resulting from the sandblasting process were effectively smoothed through subsequent electrochemical processing. Additionally, the issue of residual sand particles, which commonly arise in sandblasting procedures, was successfully addressed with the new method. The results indicated that Ti alloy samples subjected to sandblasting and electrochemical treatment in Ethaline exhibited improved surface hydrophilicity. In-vitro cell adhesion tests confirmed the potential for bio-inspired properties of DSLM-printed Ti–6Al–4V biomedical substrates achieved through the combination of sandblasting and electrochemical processing in Ethaline.